2018
DOI: 10.3390/molecules24010041
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Lignan Metabolism, Milk Enterolactone Concentration, and Antioxidant Status of Dairy Cows Fed Flaxseed

Abstract: Lignans are polyphenolic compounds with a wide spectrum of biological functions including antioxidant, anti-inflammatory, and anticarcinogenic activities, therefore, there is an increasing interest in promoting the inclusion of lignan-rich foods in humans’ diets. Flaxseed is the richest source of the lignan secoisolariciresinol diglucoside—a compound found in the outer fibrous-containing layers of flax. The rumen appears to be the major site for the conversion of secoisolariciresinol diglucoside to the enterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 106 publications
(258 reference statements)
0
35
0
2
Order By: Relevance
“…Kuhnle et al ( 90 ) reported lignans in beef (6–16 μg/100 g wet weight) and lamb (4–17 μg/100 g wet weight). Ruminal biohydrogenation leads to the conversion of dietary lignans to enterolactones, which are absorbed from the gut and deposited in tissues including milk ( 91 ) and meat ( 90 ). Manipulation of dietary phenolic compounds has been confirmed to change their contents in meat ( 92 , 93 ).…”
Section: Bioavailability Of Bioactive Compounds Of Hemp By-products Imentioning
confidence: 99%
“…Kuhnle et al ( 90 ) reported lignans in beef (6–16 μg/100 g wet weight) and lamb (4–17 μg/100 g wet weight). Ruminal biohydrogenation leads to the conversion of dietary lignans to enterolactones, which are absorbed from the gut and deposited in tissues including milk ( 91 ) and meat ( 90 ). Manipulation of dietary phenolic compounds has been confirmed to change their contents in meat ( 92 , 93 ).…”
Section: Bioavailability Of Bioactive Compounds Of Hemp By-products Imentioning
confidence: 99%
“…One COMT gene ( caffeic acid 3-O-methyltransferase ) increased 3.80-fold in Pr compared to CK. Lignan is also an important active compound in Chinese herbs, which shares a common upstream pathway with lignins and branches after the synthesis of coniferyl alcohol 30 . These results suggest that the medicinal value of D. officinale requires further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent forms of dietary lignans are secoisolariciresinol, lariciresinol, pinoresinol, and matairesinol, which are metabolized by gut microflora enzymes into enterolignans such as enterodiol and enterolactone undergoing enterohepatic circulation [ 305 , 306 ]. At least, 28 bacterial species belonging to 12 different genera (e.g., Bacteroides , Clostridium , Bifidobacterium , and Ruminococcus ) have been identified to be involved in the transformation of lignans to enterolignans [ 307 ]. Several groups have quantified the concentrations of the enterolactone metabolite in blood and urine, and reported a protective association in view of the reduction (30–45%) of cardiovascular mortality [ 308 ].…”
Section: Polyphenol Metabolitesmentioning
confidence: 99%